4-[(E)-4-Bromobenzylideneamino]-3-[1-(4-isobutylphenyl)ethyl]-1H-1,2,4-triazole-5(4H)-thione - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C(21)H(23)BrN(4)S, the 4-bromobenzylidene group is disordered over two orientations with occupancies of 0.504 (5) and 0.496 (5). One of the methyl groups of the isobutyl unit is disordered over two sites with occupancies of 0.751 (19) and 0.249 (19). The benzene rings of the isobutylphenyl and bromophenyl (major disorder component) groups form dihedral angles of 71.63 (11) and 21.8 (3)°, respectively, with the triazole ring. In the crystal, centrosymmetrically related molecules exist as centrosymmetric N—H⋯S hydrogen-bonded dimers.